2020
DOI: 10.1177/0885328220931733
|View full text |Cite
|
Sign up to set email alerts
|

PVA/anionic collagen membranes as drug carriers of ciprofloxacin hydrochloride with sustained antibacterial activity and potential use in the treatment of ulcerative keratitis

Abstract: Devices such as contact lenses and collagen shields have been used to improve the antibiotic bioavailability of eye drops formulations in the treatment of ulcerative keratitis. Nevertheless, these devices are not sustained drug delivery systems, and a combination with eye drops is necessary. In animal patients, it requires constant supervision by trained personnel to avoid device loss, which increases the cost of treatment. In this study, PVA/anionic collagen membranes containing ciprofloxacin or tobramycin we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…When CIP was loaded in the bi-functional PEG glyoxylic aldehyde -Chitosan cross-linked hydrogels at 3%, 6%, 9%, and 12% w/v polymer concentration, wherein the high polymer (9% and 12%) hydrogels demonstrated the sustained release of the drug for up to 24 h (≥ 80%) and the low polymer (3% and 6%) hydrogels had 85-95% release within 10-12 h 39 . In a study involving PVA/ anionic collagen membranes loaded with CIP, sustained release of the drug was observed reaching 95% at the end of 48 h, 40 which was considered better than the plain PVA or PVA-gelatin inserts 41,42 .…”
Section: Resultsmentioning
confidence: 98%
“…When CIP was loaded in the bi-functional PEG glyoxylic aldehyde -Chitosan cross-linked hydrogels at 3%, 6%, 9%, and 12% w/v polymer concentration, wherein the high polymer (9% and 12%) hydrogels demonstrated the sustained release of the drug for up to 24 h (≥ 80%) and the low polymer (3% and 6%) hydrogels had 85-95% release within 10-12 h 39 . In a study involving PVA/ anionic collagen membranes loaded with CIP, sustained release of the drug was observed reaching 95% at the end of 48 h, 40 which was considered better than the plain PVA or PVA-gelatin inserts 41,42 .…”
Section: Resultsmentioning
confidence: 98%
“…Antimicrobial-resistant strains of various types of bacteria derived from ocular infection have been isolated, including S. aureus, coagulase-negative staphylococci, P. aeruginosa, Corynebacterium spp., and Escherichia coli [25][26][27][28][29]. In recent years, novel alternative or additional therapeutic agents to antibiotics have been developed for ocular infections caused by antimicrobial-resistant bacteria, including antiseptic hexamidine diisethionate ophthalmic solution [30] and devices to improve the antibiotic bioavailability of eye drops such as polyvinyl alcohol/anionic collagen membranes [31] and ofloxacin-loaded polymeric nanoparticles [32]. We have previously reported the effectiveness of phage eye drops for the mouse model of P. aeruginosa keratitis [12] and others have reported a case with vancomycin-resistant S. aureus keratitis successfully treated by a bacteriophage eyedrop [33].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have been reported that around ~45% of collagen can be isolated from fishbone and ~50% from fish skin (Ahmed et al, 2020; Nagai & Suzuki, 2000). Fish collagen serves as the best alternative to land‐based collagen and is used to prepare collagen‐based films for food packaging and drug delivery (Daza et al, 2020; Jiang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%